2005
DOI: 10.1073/pnas.0502051102
|View full text |Cite
|
Sign up to set email alerts
|

Substantial DNA damage from submicromolar intracellular hydrogen peroxide detected in Hpx - mutants of Escherichia coli

Abstract: Since the discovery of catalase, it has been postulated that aerobic organisms generate enough oxidants to threaten their own fitness and, in particular, their genetic stability. An alternative is that these enzymes exist to defend the cell against more-abundant oxidants imposed by external sources. These hypotheses were tested directly through study of Hpx ؊ (katG katE ahpCF) mutants of Escherichia coli, which lack enzymes to scavenge hydrogen peroxide (H 2O2). These strains grew well in anaerobic medium but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
306
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 325 publications
(336 citation statements)
references
References 54 publications
16
306
0
1
Order By: Relevance
“…A reduction in free iron within P. gingivalis, as would result from under-expression of iron acquisition systems and over-expression of ferritin, could also be indicative of oxidative stress. Lower levels of iron in bacteria will limit the production of OH − from H 2 O 2 via Fenton chemistry [56]. Consistent with the concept that intracellular P. gingivalis are under a degree of oxidative stress is the over-expression of two alkyl hydroperoxide reductases, a thiol peroxidase and rubrerythrin, all of which can be involved in protection against oxidative stress [57,58].…”
Section: Insights Into the Intracellular Lifestyle Of P Gingivalismentioning
confidence: 71%
“…A reduction in free iron within P. gingivalis, as would result from under-expression of iron acquisition systems and over-expression of ferritin, could also be indicative of oxidative stress. Lower levels of iron in bacteria will limit the production of OH − from H 2 O 2 via Fenton chemistry [56]. Consistent with the concept that intracellular P. gingivalis are under a degree of oxidative stress is the over-expression of two alkyl hydroperoxide reductases, a thiol peroxidase and rubrerythrin, all of which can be involved in protection against oxidative stress [57,58].…”
Section: Insights Into the Intracellular Lifestyle Of P Gingivalismentioning
confidence: 71%
“…Nucleic acid damage was observed in the ahpC katA strain via loss of PCR product and an increase in spontaneous rifampin-resistant mutants. Park et al also reported an increase in the number of DNA lesions in the ahpC katG mutant of E. coli (42).…”
Section: Discussionmentioning
confidence: 97%
“…Supplementation of the media with an iron chelator or catalase enhanced the growth of Hpx Ϫ cells due to a reduction in the Fenton reaction. Furthermore, overproduction of Dps, an iron sequestration protein, complemented the growth defect of the Hpx Ϫ strain, probably due to its iron-binding activity (42).…”
mentioning
confidence: 99%
“…1) depends upon the coordination environment of the iron atom. Early measurements conducted at acid pH indicated the value was quite low (21), but at physiological pH it has been measured to range from 5000 -20,000 M −1 s −1 (13,22). The hydroxyl radical that is generated reacts at nearly diffusion-limited rates near the site of its formation.…”
Section: What Biomolecules Do Superoxide and H 2 O 2 Damage?mentioning
confidence: 99%
“…These strains grew well anaerobically but exhibited a variety of aerobic growth defects that derived from the accumulation of endogenous O 2 − . Similarly, E. coli catalase/ peroxidase mutants are poisoned by the micromolar doses of intracellular H 2 O 2 that accumulate (13,14). A key goal has been to track these defects back to the biochemical lesions that cause them.…”
Section: What Biomolecules Do Superoxide and H 2 O 2 Damage?mentioning
confidence: 99%